SIGNATURES OF THE HIGHLY SIDEROPHILE ELEMENTS IN THE SNC METEORITES AND MARS: A REVIEW AND PETROLOGIC SYNTHESIS - Jones J.H.; Neal C.R.; Ely J.C. (My University, 2003)
We have evaluated the highly siderophile element (HSE) signatures of the martian (SNC) meteorites using new and literature data. These Ir and Os concentrations correlate with the Mg# [molar Mg/(Mg+Fe)], Cr and Ni, suggesting that olivine or chromite acts as a host for compatible siderophiles. Our analysis agrees with others who have suggested that the martian mantle has chondritic relative abundances of siderophiles. We also agree that, unlike the Sr and Nd isotopic systems, there is no evidence from Os isotopes for crustal assimilation. Comparisons of the siderophile element ratios of ALH 84001 to younger SNCs give no indication of a change in the martian siderophile element pattern over time.
Keywords: SNC METEORITES; SIDEROPHILE ELEMENTS; OS ISOTOPES; CORE FORMATION; MARS GEOCHEMISTRY